Evidence‐based pathways to intervention for children with language disorders. Issue 1 (25th April 2018) - Ebbels, Susan H.; McCartney, Elspeth; Slonims, Vicky; Dockrell, Julie E.; Norbury, Courtenay Frazier
Abstract: Background: Paediatric speech and language therapist (SLT) roles often involve planning individualized intervention for specific children, working collaboratively with families and education staff, providing advice, training and coaching and raising awareness. A tiered approach to service delivery is currently recommended whereby services become increasingly specialized and individualized for children with greater needs. Aims: To stimulate discussion regarding delivery of SLT services by examining evidence regarding the effectiveness of (1) intervention for children with language disorders at different tiers and (2) SLT roles within these tiers; and to propose an evidence‐based model of SLT service delivery and a flowchart to aid clinical decision‐making. Methods & Procedures: Meta‐analyses and systematic reviews, together with controlled, peer‐reviewed group studies where recent systematic reviews were not available, of interventions for children with language disorders are discussed, alongside the differing roles SLTs play in these interventions. Gaps in the evidence base are highlighted. Main Contribution: The service‐delivery model presented resembles the tiered model commonly used in education services, but divides individualized (Tier 3) services into Tier 3A: indirect intervention delivered by non‐SLTs, and Tier 3B: direct intervention by an SLT. We report evidence for intervention effectiveness, which children might best be served by each tier, the role SLTs could take within each tier and the effectiveness of these roles. Regarding universal interventions provided to all children (Tier 1) and those targeted at children with language weaknesses or vulnerabilities (Tier 2), there is growing evidence that approaches led by education services can be effective when staff are highly trained and well supported. There is currently limited evidence regarding additional benefit of SLT‐specific roles at Tiers 1 and 2. With regard to individualized intervention (Tier 3), children with complex or pervasive language disorders can progress following direct individualized intervention (Tier 3B), whereas children with milder or less pervasive difficulties can make progress when intervention is managed by an SLT, but delivered indirectly by others (Tier 3A), provided they are well trained and supported, and closely monitored. Conclusions & Implications: SLTs have a contribution to make at all tiers, but where prioritization for clinical services is a necessity, we need to establish the relative benefits and cost‐effectiveness at each tier. Good evidence exists for SLTs delivering direct individualized intervention and we should ensure that this is available to children with pervasive and/or complex language disorders. In cases where service models are being provided which lack evidence, we strongly recommend that SLTs investigate the effectiveness of their approaches.